GLASGOW COMA SCALE (GCS), TEKANAN DARAH DAN KADAR HEMOGLOBIN SEBAGAI PREDIKTOR KEMATIANPADA PASIEN CEDERA KEPALA - S Sumarno; Moch. Hidajat; Ika Setyo Rini (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2016)
The number of incidence and mortality of patients with traumatic brain injury (TBI) is high, so it is called for better service, on the other hand healthcare care facilities, particularly bed of intensive care unit (ICU) limited. So often the hospital should perform a selection against patients. Mortality predictors can be used as tool for selection. The aims of this research is to gain a predictive model of mortality in isolativeTBI patients using a standardized examination in Emergency Department. Design of this study is a observational study with prospective approach. Respondents totaled 49 person byconsecutive sampling.The results of this research show that there is a correlation between all the independence variables with mortality of the patient.GCS (p<0,001, r=0,732), TDS (p=0,005, r=0,420), MAP (p=0,005, r=0,429), Hb (p=0,048, r=0,272). The result of logistic regression showed that GCS is the most dominant factor related to patient mortality is GCS (p=0,002, correlation coefisient = - 0,906). Keywords : Traumatic brain injury, mortality predictor, GCS, components of GCS